Reactive distillation for the production of methoxy propyl acetate: experiments and simulation - Gadekar-Shinde, Shambala; Reddy, Bhoja; Khan, Mohammad; Chavan, Sanjay; Saini, Dauiat; Mahajani, Sanjay (Industrial & Engineering Chemistry Research, 2017)
Propylene glycol methyl ether acetate is an industrially important solvent. In this work, we study the applicability of reactive distillation (RD) for its synthesis in the presence of an ion-exchange resin, Amberlyst 15, as a catalyst. Simultaneous separation of water during the course of reaction shifts the reaction in the forward direction, which renders cost effectiveness and compactness to the process. The presence of an azeotrope between methoxy propanol and water complicates the separation, leading to a loss of reactants in the product streams, thereby hampering both conversion and purity. Toluene is thus used as an entrainer to further intensify the process. In this work, the intrinsic kinetic parameters are determined from batch reactor data, and used subsequently to simulate the column performance. An experimentally validated simulator is used to examine the effect of various operating and design parameters. Reactant and product losses are minimized to negligible levels and a significant increase in the conversion is realized.

Mechanistic modeling of size exclusion chromatography-assisted in vitro refolding of the recombinant biosimilar teriparatide (PTH-34) - Ughade, Santosh; Rana, Sunil; Nadeem, Mohd; Kumthekar, Rupali; Mahajani, Sanjay; Bhambure, Rahul (ACS Omega, 2024)
In vitro protein refolding is one of the critical unit operations in manufacturing recombinant peptides expressed using Escherichia coli as host cells. This study is focused on designing size exclusion chromatography-assisted in vitro refolding process for biosimilar recombinant parathyroid hormone. Inclusion bodies (IBs) of recombinant parathyroid hormone were solubilized at higher pH, and in vitro refolding was performed using size exclusion chromatography. In the first part of the investigation, DoE-based empirical optimization was performed to achieve a higher refolding yield for a biosimilar recombinant parathyroid hormone. The effect of solubilized inclusion body (IB) feed volume, concentration of IBs, and residence time on in vitro refolding of recombinant teriparatide was studied using the Box-Behnken design. Size exclusion chromatography (SEC)-assisted in vitro refolding was performed at 8 C-degrees at pH 10.5 by using 20 mM Tris buffer. The maximum refolding yield of 98.12% was achieved at feed volume (12.5% of CV) and 20 mg/mL inclusion body (IB) concentration with a residence time of 50 min and a purity of 66.1% based on densitometric analysis using SDS-PAGE. In the latter part of the investigation, the general rate mechanistic model framework for size exclusion chromatography was developed and validated with the experimental results. The developed model helped in the accurate prediction of the elution volumes and product yield. The developed model also helps to predict the elution performance of a scalable column a priori. Post in vitro refolding, the formation of the native peptide structure was examined using various orthogonal analytical tools to study the protein's primary, secondary, and tertiary structures. The developed hybrid process development approach is a valuable tool toachieve high-yield, scalable refolding conditions for recombinant proteins without disulfide bonds.